Kejahatan Dunia Maya Terkait Hoaks Saat Pandemi Covid 19 - Fitri Kartika; Anggraeni Endah Kusumaningrum (Pusat Riset dan Inovasi Nasional, 2022)
Crimes that often occur in cyberspace are crimes that are relatively new, cybercrime is growing rapidly along with the development of internet technology that is happening today. The spread of hoaxes during the Covid 19 pandemic has become a big problem because many people believe hoaxes, causing the handling of Covid 19 to be very slow and causing many victims. The Covid 19 pandemic has forced all people in the world, including Indonesia, to be comfortable living side by side with Covid 19. This research uses a normative legal research method using a statutory approach. The main source of this research is regulations. The results of this study indicate several crimes that can be used as protection by consumers who experience losses due to fake news amid the Covid 19 pandemic, namely Article 14 paragraph (1), paragraph (2), Article 15 Article 14 paragraph (1) and Article 45A paragraph (1). ) and (2), and article 28 of Law Number 11 of 2008 concerning Information and Electronic Transactions.